FEATURES OF VISUALIZATION OF LOGO OF MUSICAL BANDS OF INDEPENDENT UKRAINE - Міхєєва, Л. В. (Art and Design, 2020)
The purpose of this article is to identify the distinctive features of the visual language of creating logos of musical band under the influence of cultural and socio-political events. Methodology. The research method is to observe and compare design objects. For analysis, the logos of music bands were taken, the list of which consists of more than 180 groups that existed and existed on the Ukrainian music space for at least two years. The chronological boundaries of the study are determined by the period of Independence of Ukraine (1991 – to date). Results. The trends of the visual component of logos have been divided into several historical periods. The visual language of each of the designated periods is traced, the characteristic features and tendencies of the visual series are revealed. The typology of logos of music band by graphic and semantic loading is deduced as the means of communication that influence the creation of the image of the music band and its brand. Some types of logos are considered as a means of identifying a music band. Scientific novelty. There is a systematization of logos of music bands according to certain characteristics, elements of visual languages, graphic components. Cases of creating a recognizable brand of a music bands that have no established logo but have existed for a long time due to the fan audience that perceives their creativity are considered separately. It is argued that the musical style in which a certain team works on the functioning of a brand of a music bands as a whole is the most influential factor in creating elements of its visual language. Practical significance. The proposed systematization and conclusions presented in the article can be used in scientific studies related to the further study of the elements of graphic identification; in the educational process of studying the subject of research; in the preparation of training and methodological manuals in graphic design.